2010
DOI: 10.1111/j.1471-4159.2009.06511.x
|View full text |Cite
|
Sign up to set email alerts
|

Tau oligomers and aggregation in Alzheimer’s disease

Abstract: J. Neurochem. (2010) 112, 1353–1367. Abstract We are analyzing the physiological function of Tau protein and its abnormal pathological behavior when this protein is self‐assemble into pathological filaments. These aggregates of Tau protein are the main components in many diseases such as Alzheimer’s disease (AD). Recent studies suggest that Tau acquires complex oligomeric conformations which may be toxic. In this review, we emphasized the possible phenomena implicated in the formation of these oligomers. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 142 publications
(168 reference statements)
2
107
1
Order By: Relevance
“…This further indicates that a nitrocatechol pharmacophore plays a major role in preventing AcPHF6 aggregation. Furthermore, a tolcapone derivative, methylbenzophenone (13), that lacks the critical nitrocatechol moiety failed to prevent AcPHF6 aggregation validating the critical nature of a nitrocatechol pharmacophore in preventing tau-hexapeptide aggregation ( Figure S5, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This further indicates that a nitrocatechol pharmacophore plays a major role in preventing AcPHF6 aggregation. Furthermore, a tolcapone derivative, methylbenzophenone (13), that lacks the critical nitrocatechol moiety failed to prevent AcPHF6 aggregation validating the critical nature of a nitrocatechol pharmacophore in preventing tau-hexapeptide aggregation ( Figure S5, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Most recent evidence suggests that oligomers and probably also protofibrils are toxic to neurons by disrupting synaptic function, membrane permeability, calcium homeostasis, gene transcription, mitochondrial activity, autophagy, and/or endosomal transport [18][19][20][21]. Moreover, recent studies have shown that propagation and seeding of Aβ, tau, and α-syn in a prion-like manner might also contribute to neurodegeneration [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Other stereological studies show that neuronal loss actually exceeds NFT formation (Gomez-Isla et al 1997, Terry 2000, van de Nes et al 2008, Vogt et al 1998. This and the exciting data published in the last half decade, emerging from biochemical, cell-based and transgenic mouse studies suggest that pre-filament forms of tau may be the most toxic and pathologically significant form of tau aggregates (Brunden et al 2008, Marx 2007, Meraz-Rios et al 2009). This evolutionary transition was overdue in the tau field and similar to the transition witnessed for A in the last 15 years driven by the characterization of A intermediate species and their crucial role in A -mediated toxicity (Harper et al 1997, Roher et al 1993, Walsh & Selkoe 2004, Walsh & Selkoe 2007.…”
Section: Tau Oligomers Toxicity In Vivomentioning
confidence: 93%